The propensity to have children in Hungary, with some examples from other European countries - Berde, Éva; Drabancz, Áron (Frontiers in Sociology, 2022)
In most countries around the world, the total fertility rate (TFR) has been on a downward trend over recent decades. In the developed, and many less developed countries this has led to the TFR being consistently below the replacement level of 2.1 over the long term, leading to population decline in the absence of immigration. Many European governments, including that of Hungary, are spending a significant proportion of GDP on family support to prevent fertility decline. Despite these efforts, we have not seen any significant increase in the TFR. In this article, we explain the decisions of families not to have children by using a more stringent formulation of Becker's original quantity-quality trade-off. We point out that increasing family support expenditure has not achieved its goal. While huge financial effort has been made to increase fertility rates, insufficient attention has been paid to alleviating the burden of the growing elderly population.